Fabrication and Analysis of a Triple Band Patch Antenna: Fabrication and Analysis of a Triple Band Patch Antenna - Ahmad, Gulzar; Sultan, Asif; Khan Babar, M. Inayatullah; Ashraf, Majid; Jan, Tariqullah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The paper presents the design and fabrication of a patch antenna of hexagonal shape on FR-4 lossy substrate of 1.6mm thickness. To achieve multi bands an inverted C-Shaped cut was etched in the patch. The antenna has over all dimensions of 61×48×1.6mm3. Microstrip line feed has been used for the excitation purpose of the antenna. Measurements of Return Loss (RL), Voltage Standing Wave Ratio (VSWR) and Input Impedance were taken using Vector Network Analyzer (VNA) of Rohde & Schwarz Company. The antenna offered three bands with resonant frequencies of 3.36GHz, 4.06GHz and 7.01GHz lying in S and C bands. The -10dB bandwidths achieved are 60MHz (3.340GHz-3.400GHz), 76MHz (4.033GHz-4.109GHz) and 754MHz (6.391GHz-7.145GHz) with corresponding return losses of 20.23dB, 16.30dB and 25.24dB respectively. VSWR of the antenna for all the above mentioned three bands remains below 2. The antenna can be used for different military and commercial applications in S and C bands.